Microstructure evolution of in-situ alloyed and heat-treated stainless steels processed by DED-LB/M - Maier, Andreas; Tangermann-Gerk, Katja; Frankl, Sebastian; Bartels, Dominic; Roth, Stephan; Schmidt, Michael (Materials Today Communications, 2025)
To date, the number of stainless steels available for additive manufacturing (AM) is limited and the range of material properties achievable by AM is inadequate. This limits the industrial applicability of AM technologies such as laser-based directed energy deposition of metals (DED-LB/M). However, the approach of in-situ alloying enables efficient alloy design for AM. This study provides novel insights into the microstructure formation of in-situ alloyed stainless steels manufactured by DED-LB/M. Therefore, 1.4462 duplex stainless steel (DSS) powder was blended with chromium and nickel powder to adjust the chemical composition and stabilize either ferrite or austenite formation. Defect-free specimens were generated and then heat-treated by solution annealing and quenching. Chemical analysis demonstrated that the target composition could be precisely adjusted via in-situ alloying. In-situ alloying of DSS with ferrite- or austenite-stabilizing elements shifted the phase ratio from a ferritic-austenitic (50%:50%) duplex microstructure to a predominantly ferritic (88% ferrite) or a completely austenitic microstructure (100% austenite). The measured phase fractions (electron backscattered diffraction, EBSD) of all compositions investigated were in good agreement with the initially calculated phase equilibria. Optical light microscopy and EBSD analysis also showed that the dominating austenite morphology changes along with the phase ratio. In addition, the phase-specific average grain sizes and textures were significantly influenced by Cr- or Ni-additions. Increasing the ferrite fraction from 50% to 88% enhanced the material hardness from 245 ± 4 HV10 to 270 ± 6 HV10. In contrast, increasing the austenite fraction from 50% to 100% reduced the material hardness to 173 ± 4 HV1
Keywords: Directed energy deposition; Additive manufacturing; In-situ Alloying; Stainless steels; Microstructure; Hardness